Tax loss amortization of companies in Slovakia - Anna Bánociová; Slavomíra Ťahlová (Journal of Risk and Financial Management, 2020)
The purpose of this article is to research how companies optimize income tax with the ambition to maintain the achieved sales and profits at the highest possible level. Its purpose is to find out whether companies in Slovakia compensate for higher tax liability by tax loss amortization to reduce their income tax payable. Based on the review of literature from the field of legislation concerning the tax loss amortization by using the descriptive statistics of selected corporate and tax indicators, the companies are monitored in order to capture their behavior in paying income tax. The methods of deduction and synthesis are used in this article. The observed corporate and tax indicators are focusing on the relationship between the tax liability arising from corporate income tax, amortized tax losses, and the amount of tax payable in Slovakia in the period from 2015 to 2018. Tax loss can be considered as a tool for tax optimization, which is used by companies in all countries of the European Union, while the scope of its applicability is often limited by a time horizon. The amortization of tax losses has an impact on the amount of tax levied and the subsequent income tax payable, while the possibility to use this tool of tax optimization is influenced by the changing legislation in the period under review.
Keywords: 330; corporate income tax; tax loss; tax loss amortization; tax optimization